2022
DOI: 10.1177/1037969x221132565
|View full text |Cite
|
Sign up to set email alerts
|

The fall of Roe v Wade, the US anti-abortion movement and its influence in Australia

Abstract: This article examines the overturning of the landmark US Supreme Court decision of Roe v Wade, the precedent which conferred federal constitutional protection on the right to abortion. It looks at the US anti-abortion movement which worked for decades to overturn Roe v Wade and the degree to which Australian law is vulnerable to its influence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In this study, a confounding issue was that the survey was open for participation at the time when Roe v Wade was overturned in the United States (June 24, 2022), which dominated the news and social media platforms internationally 62 . It is not possible to determine how this may have influenced attitudes reported in this study particularly those around matters concerning privacy, autonomy, and the personhood of fetuses and embryos.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, a confounding issue was that the survey was open for participation at the time when Roe v Wade was overturned in the United States (June 24, 2022), which dominated the news and social media platforms internationally 62 . It is not possible to determine how this may have influenced attitudes reported in this study particularly those around matters concerning privacy, autonomy, and the personhood of fetuses and embryos.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, a confounding issue was that the survey was open for participation at the time when Roe v Wade was overturned in the United States (June 24, 2022), which dominated the news and social media platforms internationally. 62 It is not possible to determine how this may have influenced attitudes reported in this study particularly those around matters concerning privacy, autonomy, and the personhood of fetuses and embryos. At the time of the overturned legislation, debates and conversations around women's health and reproductive rights increased in Australia and included both condemnation and support for safe accessible and legal abortions.…”
mentioning
confidence: 93%
“…This analysis adapted Levesque et al's in uential framework of patient-centred access to healthcare(3) to abortion access during the COVID-19 pandemic. We found that the framework facilitated a nuanced examination of the multifaceted and intersecting factors that in uence access to abortion -a historically criminalised and still stigmatised service (15,49). This adaption of Levesque's framework can be applied in different contexts to understand experiences of access to stigmatised health services and examine healthcare access in pandemic or other disaster conditions.…”
Section: Discussionmentioning
confidence: 96%
“…When Roe v Wade was overturned by the United States Supreme Court in 2022, enraged crowds took to the streets advocating for abortion access 11 . A series of Bills were then released advocating for fetal personhood in high income Organisation for Economic Co‐operation and Development (OECD) countries, including Canada and Australia 12 . By setting precedents for fetal personhood, they seek to complicate and over‐regulate abortion access.…”
mentioning
confidence: 99%